Problem-Based Learning Model and Motivation on Students’ Critical Thinking Ability in Natural and Social Science Learning - Fadhilah; Miaz, Yalvema; Fitria, Yanti; Zen, Zelhendri (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to explore the problem-based learning  model and motivation on students' critical thinking ability in Natural and Social Science earning. The research method was quantitative with a quasi-experimental design, adopting a nonequivalent control group design. The research was carried out at SD Negeri 13 Padang Gelanggang. The research population included all the 5th grade students, with the sample selected using random sampling techniques. The research subjects consisted of 18 students in the experimental class and 18 students in the control class. Data were collected through critical thinking ability tests and learning motivation questionnaires. The analysis results using the independent sample t-test and two-way ANOVA test showed that the problem-based learning model had a significant effect on increasing students' critical thinking abilities. It indicated that the critical thinking abilities of students who studied with the problem-based learning (PBL) model were better than those who studied with the conventional approach.